The handbook of blended learning : global perspectives, local designs. - Bonk, Curtis J., ....-; Graham, Charles Ray, ....- (San Francisco : Pfeiffer, 2006)
This comprehensive resource highlights the most recent practices and trends in blended learning from a global perspective and provides targeted information for specific blended learning situations. You'll find examples of learning options that combine face-to-face instruction with online learning in the workplace, more formal academic settings, and the military. Across these environments, the book focuses on real-world practices and includes contributors from a broad range of fields including trainers, consultants, professors, university presidents, distance-learning center directors, learning strategists and evangelists, general managers of learning, CEOs, chancellors, deans, and directors of global talent and organizational development. This diversity and breadth will help you understand the wide range of possibilities available when designing blended learning environments.
Keywords: Blended learning; Computers -- Onderwijs; Nieuwe technologie -- Hoger onderwijs; Onderwijs en internet; Onderwijsvernieuwing -- Hoger onderwijs